First record of leucospis signifera bouček, 1974 (Insecta: Hymenoptera: Leucospidae) in the São Paulo State, Brazil - Perioto, Nelson W. [UNESP]; Lara, Rogéria I.R. (My University, 2012)
The present note extends the geographic range of Leucospis signifera Bouček, 1974 farther to the Northeast, reaching the State of São Paulo, based on the examination of four females collected at Jataí Ecological Station, municipality of Luiz Antônio, São Paulo State, Brazil. The present finding indicates that L. signifera is associated with dry ecosystems, at least in part of its geographic distribution. © 2012 Check List and Authors.
Keywords: Hymenoptera; Insecta; Leucospidae; Leucospis